Fabrication of Silicon Prosthesis For a Partial-Auricular Defect in an Eight- Year-Old Patient: A Case Report - Rai, A; Poudyal, J; Parajuli, PK; Dali, M; Suwal, P; Koirala, B (Journal of Nepalese Prosthodontic Society, 2022)
Loss of the external ear can be congenital or acquired due to accidental trauma or malignant disease. Patients usually seek the prosthetic treatment for defects in head and face area when they feel that their function or esthetics are compromised. Literatures show that most of the prosthesis are fabricated in adult patients. Most of the time, dependence of the children on the parents for decision making and finances overshadows the psychological needs and perspectives of children. Present care report highlights the fabrication of silicone prosthesis for partial auricular defect in an eight-year-old child patient, who was conscious about his appearance due to the external defect in his pinna.